»Kritik im Handgemenge«: Die Marx'sche Gesellschaftskritik als politischer Einsatz - Schönfelder, Anna-Sophie; Spekker, Matthias; Bohlender, Matthias (transcript, 2018)
Marx within a political context – This book is about a new approach of how to see Marx` social criticism more from the perspective of its political commitment in a scuffle.